(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To evaluate the effect of SAMAN joint tablets on bearing capacity, and knee morphology in a model of osteoarthritis induced by monosodium iodoacetate (MIA). Method: 50 Wistar white rats, divided into 05 lots, 10 mice/lot: Physiological control group; 04 lots (Model/Treatment 1/Treatment 2/Reference lot) caused osteoarthritis by MIA, after 1 week of MIA injection to mice drinking distilled water/joint SAMAN dose 476mg/kg/day and 952mg/kg /day/ indomethacin. Results: SAMAN joint tablets at doses of 476mg/kg/day and 952mg/kg/day had the effect of increasing the distribution of weight tolerance of the hind legs (p < 0.001 and p < 0.01) compared with the model lot; p < 0.001 compared to before drug use); Reduces inflammatory and degenerative knee joint damage on HE-stained knee histopathology, reduces the score of knee osteoarthritis histopathological damage (p < 0.01 compared to the model lot). These effects of SAMAN joint tablets were comparable to those of indomethacin at a dose of 2mg/kg/day. Conclusions: SAMAN joint tablets have analgesic, anti-inflammatory and anti-degenerative effects on osteoarthritis models.